Peran Motivasi Guru Terhadap Siswa Kelas VIII Pada Mata Pelajaran Ips Terpadu di SMP Negeri 2 Halmahera Barat - Gaus, Djulaiha (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to determine the role of teacher motivation in eighth-grade students' learning of Integrated Social Studies (IPS) at SMP Negeri 2 West Halmahera. Learning motivation is a crucial factor influencing student enthusiasm, attention, and learning outcomes. As facilitators and motivators in the learning process, teachers are responsible for creating a pleasant learning environment and encouraging students to be active and enthusiastic in participating in lessons. The research method used was a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation. The study subjects consisted of social studies teachers and eighth-grade students. The results showed that teacher motivation, whether in the form of praise, rewards, or personal approaches, had a positive impact on increasing student interest and participation in learning. Furthermore, varied and relevant learning strategies have also been shown to increase student engagement in the teaching and learning process. From these findings, it can be concluded that teacher motivation plays a crucial role in supporting student learning success. Teachers who are able to motivate students effectively can create a conducive learning environment, increase enthusiasm for learning, and encourage the achievement of more optimal learning outcomes. Keywords: Teacher Motivation